(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Twenty eight local rice landraces were assessed for eleven morphological traits for the improvement of salt tolerance ability of rice genotypes. Genotypic variance (σ2g), phenotypic variance (σ2p), phenotypic co-variance (PCV), genotypic co-variance (GCV), heritability, genetic advance, genetic advance as a percentage of mean, correlation coefficient and path coefficient were estimated. For all the traits, PCV was higher than the GCV indicating that they were controlled by non-additive gene action and selection for the improvement of these traits would be promising. Among the traits, survival rate of plant exhibited high estimates of PCV (460.72) and GCV (324.73) indicated wide range of variability for these traits where lowest phenotypic coefficient of variation (PCV) and genotypic coefficient of variation (GCV) where low PCV and GCV were observed for root dry weight (0.17 & 0.12) followed by shoot dry weight (0.31 & 0.16) and total number of roots (0.61 & 0.34) indicating lack of inherent variability and limited scope for improvement through selection for these traits among the genotypes. Highest heritability had observed in all traits except chlorophyll content and root length and maximum value of heritability was noticed for shoot length (75.96%). High heritability along with high genetic advance was noticed for survival rate of plant (31.14%) followed by live leaves percentage (11.98) and the lowest genetic advance was found in root dry weight (0.58) and shoot dry weight (0.58). Correlation study revealed that significant negative correlations at both phenotypic and genotypic level exist between standard evaluation score (SES) and survival rate (%), root length, shoot length, root fresh weight, root dry weight and shoot dry weight at the seedling stage further confirmed the importance of these parameters as useful selection criteria for screening for salt tolerance rice genotypes. Path analysis revealed that the root length (0.487), root dry weight (0.394) and shoot dry weight (0.047) had direct positive effect on standard evaluation score at genotypic level where live leaves (%) per plant (0.168), total number of roots (0.006), chlorophyll content (0.243) and shoot fresh weight (0.102) had direct positive effect on standard evaluation score at phenotypic level. From the correlation and path analysis it can be concluded that root length, root dry weight and shoot dry weight would be more promising for the improvement of salt tolerance in rice genotypes J. Bangladesh Agril. Univ. 16(1): 41-46, April 2018